Code Switching In Classroom Discourse: A Sociolinguistic Study - Reni Yulandari; Lalu Muhaimi; Atri Dewi Azis (Jurnal Ilmiah Profesi Pendidikan, 2018)
This research attempts to find out the most frequently used type and the function of codeswitching, also the implication of code-switching towards the teaching and learning situation in two classrooms of the fourth semester at English Education Department, University of Mataram. The descriptive qualitative method was adopted in conducting this method. The data collection was done through observation, recording and interview. The results of this study showed that three are types of code-switching are found in 129 utterances which contain code-switching in the classrooms.  The most frequently used type was Intra-sentential switching, which appeared in 70,5% of the utterances, followed by tag switching (16,2%) and inter-sentential switching (13,1%). There were two functions of code-switching found in this study, they ware translation and communicative function which included motivating, giving feedback, checking comprehension, joking, and expressing state of mind. The implication of code-switching in teaching and learning situation was considered as one of the good strategies to built an efficient and conducive teaching and learning situation in the classrooms, as it is necessary in certain condition and still hard to avoid since it is helpful for material explanation as well as an ice breaker.